1997
DOI: 10.1016/s0009-2614(97)00362-x
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular interaction of photoexcited Cu(TMpy-P4) with water studied by transient resonance Raman and picosecond absorption spectroscopies

Abstract: A photoinduced complex between Cu(TMpy-P4) and water molecules, reversibly axially coordinated to the central metal, was observed in picosecond transient absorption and nanosecond resonance Raman experiments. This complex is rapidly created (z~ = 15 + 5 ps) in the excited triplet (~r, ~r * ) state of Cu-porphyrin, and the subsequent relaxation is proposed to proceed via two parallel pathways. One is fast and efficient (>/90% of molecules), and presumably involves a (ax, d) charge-transfer state. The second pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Because of the efficient triplet formation, investigations of this excited state revealed the presence of many triplet state phenomena, such as the presence of a lower-energy charge-transfer state (ring!metal) operating on the ps timescale, [29] the formation of an exciplex with water (among other donors) [30] also being formed on the ps timescale ((15 AE 5) ps), [31] the formation of singlet oxygen (see, for example, ref. [32]), the T 1 -T 1 energy transfers to free bases, [33] and enhancement of intersystem crossing by through-bond exchange interactions.…”
Section: Spectroscopy and Photophysicsmentioning
confidence: 99%
“…Because of the efficient triplet formation, investigations of this excited state revealed the presence of many triplet state phenomena, such as the presence of a lower-energy charge-transfer state (ring!metal) operating on the ps timescale, [29] the formation of an exciplex with water (among other donors) [30] also being formed on the ps timescale ((15 AE 5) ps), [31] the formation of singlet oxygen (see, for example, ref. [32]), the T 1 -T 1 energy transfers to free bases, [33] and enhancement of intersystem crossing by through-bond exchange interactions.…”
Section: Spectroscopy and Photophysicsmentioning
confidence: 99%
“…1 ns. 107 They assigned the transient Raman signals to the latter component which they identified as a d-d excited state with an axially bound water. They rationalized the low yield (φ e 0.1) of the d-d excited-state adduct in terms of competitive deactivation via a five-coordinate CT state.…”
Section: E Exciplex Formationmentioning
confidence: 99%
“…A subsequent paper by Kruglik et al reported that the exciplex involving a bound water molecule forms in low yield and has a lifetime in excess of a nanosecond. 107 They also concluded that the adduct exhibits a distinctive blue shift in its Soret band.…”
Section: F Transient Raman Studiesmentioning
confidence: 99%
“…RR spectra were recorded several times, independently at three different nanosecond Raman spectrometers available in our laboratories in Minsk, 22 Paris, 26 and Enschede. 53 All systems were based on Q-switched Nd:YAG lasers, used as pump source for other laser devices such as dye lasers, Raman shifters, and frequency mixers. All Raman spectra were collected in using nearly backscattering geometries.…”
Section: Methodsmentioning
confidence: 99%
“…Raman scattering signal was dispersed either by a double diffraction DFS-52 22 and Jobin-Yvon HG2S 26 monochromator (in the case of single-channel detection system) or by the Spex Triplemate 1877 polychromator in combination with a PAR-1421 multichannel array detector. 53 Spectral resolution in all experiments was typically ca. 5-7 cm -1 .…”
Section: Methodsmentioning
confidence: 99%